The Yellow Book-Based Fikih Learning Method at the Waratsatul Anbiya Islamic Boarding School - Yozi, Satri; Khairat, Annisaul; Admalinda, Admalinda (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
This research reveals how the Jurisprudence learning method uses the yellow book at the Waratsatul Anbiya Islamic Boarding School, Solok City. The purpose of this study was to find out how the fiqh learning method uses the Yellow Book at the Waratsatul Anbiya Islamic Boarding School, Solok City. This research qualitative uses research methods with the type of field research research that is descriptive qualitative. Sources of data are teachers of the Yellow Book of Jurisprudence subjects and other data sources. Data collection techniques namely observation, interviews, and documentation. The data analysis used was selecting data, grouping data, content analysis, and drawing conclusions. The results showed that the method used in the implementation of fiqh learning using the book was to use the combined bandongan method (students listened to or followed what the ustadz / ustadzah said), sorogan ( ustadz / ustadzah listened/followed what the students said) , rote (method to remember teaching materials), and discussion methods (as problem solving of the material studied). The reason this method is applied is because it can make it easy for students to understand or understand in terms of the meaning in learning fiqh using the yellow book.